A comparative study of the development of sports professionals in Chinese and Canadian Universities - Wang, R. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The university is a base for developing sports professionals and in China`s modern context, athletes need to be willing to take on the challenges that professional sport can bring. There is much to learn from more developed nations in these areas of professional development, many of whom have been involved at this level for considerable time. As in other countries, sports professionals in China are able to share and gain ideas from other countries and a useful strategy in this process is to investigate and compare the level of developmental with China and other countries. As such, the purpose of this study was to investigate and compare sport development in Canada and China. Methods Review and analysis of relevant documents with respect to the procedures and strategies implemented for running schools in Canada and China. Results Freeing the mind and being open to new ideas can help to improve performance in individuals. In Canada there are laws on physical education which allow universities the freedom to make decisions as to how to run the school, how to arrange the specialized fields of study and what kinds of courses to offer. An enlargement of the range of the specialized fields of study could be beneficial. At a nation wide level, changes for new scientific evidence need to be implemented.